Computational biomechanics of human brain with and without the inclusion of the body under different blast orientation. Issue 9 (3rd July 2016) - Salimi Jazi, Mehdi; Rezaei, Asghar; Azarmi, Fardad; Ziejewski, Mariusz; Karami, Ghodrat
Abstract: Three different human head models in a free space are exposed to blast waves coming from four different directions. The four head–neck–body models composed of model a, with the neck free in space; model b, with neck fixed at the bottom; and model c, with the neck attached to the body. The results show that the effect of the body can be ignored for the first milliseconds of the head–blast wave interactions. Also one can see that although most biomechanical responses of the brain have similar patterns in all models, the shear stresses are heavily increased after a few milliseconds in model b in which the head motion is obstructed by the fixed-neck boundary conditions. The free-floating head model results are closer to the attached-body model.